A large arteriovenous fistula steals a considerable part of systemic blood flow during veno-arterial extracorporeal circulation support in a porcine model - Valerianova, A.; Mlcek, M.; Kittnar, O.; Grus, T.; Tejkl, L.; Lejsek, V.; Malik, J. (Frontiers in Physiology, 2023)
Background: Veno-arterial extracorporeal membrane oxygenation (V-A ECMO) is one of the most frequently used mechanical circulatory supports. Distribution of ECMO flow depends (similarly as the cardiac output distribution) on regional vascular resistance. Arteriovenous fistulas (AVFs), used frequently as hemodialysis access, represent a low-resistant circuit which steals part of the systemic perfusion. We tested the hypothesis that presence of a large AVF significantly changes organ perfusion during a partial and a full V-A ECMO support. Methods: The protocol was performed on domestic female pigs held under general anesthesia. Cannulas for V-A ECMO were inserted into femoral artery and vein. The AVF was created using anther two high-diameter ECMO cannulas inserted in the contralateral femoral artery and vein. Catheters, flow probes, flow wires and other sensors were placed to perform continuous monitoring of haemodynamics and organ perfusion. Steps with increasing ECMO flow in beating heart and in ventricular fibrillation (VF) with closed and opened AVF were performed. Results: Opening of a large AVF (blood flow ranging from 1.1 to 2.2 L/min) resulted in decrease of effective systemic blood flow by 17-30 % (p < 0.01 for all steps). This led to a significant decrease of carotid artery flow (ranging from 13 to 25 % after AVF opening) in VF and in partial ECMO support. Cerebral tissue oxygenation measured by near infrared spectroscopy also decreased significantly in all steps. These changes occurred even with maintained perfusion pressure. Changes in coronary artery flow were driven by changes in the native cardiac output. Conclusions: A large arteriovenous fistula can completely counteract the V-A ECMO support unless maximal ECMO flow is applied. Cerebral blood flow and oxygenation are mainly compromised by the effect of the AVF. These effects could influence brain function in patients with AVF on VA-ECMO.